Fear of Falling among Elderly Individuals with Various Medical Conditions - T.K. Konovalchik (Клиническая и специальная психология)
Fear of falling is a significant problem among the elderly population, leading to a decrease in quality of life. Research on this phenomenon has been actively conducted abroad since the 1990s, starting with the works of N. Lach, M. Lachman, and M. Tinetti. In Russia, there is practically no research on the fear of falling. Objective. This study is dedicated to systematizing and summarizing existing data on the fear of falling among the elderly with various health conditions. Methods. Theoretical analysis of contemporary research on the fear of falling among the elderly. Results and Conclusions. It was found that there is no reliable data on the correlation between sensory deficits and fear of falling, although reduced vision, hearing, and proprioceptor sensitivity increase the risk of falling. Fear of falling can develop in physically well-functioning elderly individuals with high levels of anxiety, and depression is secondary to fear of falling. The presence of pronounced character accentuations can contribute to the development of fear of falling and even panic attacks. In Parkinson`s disease, the risk of falling increases in cognitively intact patients, and fear of falling is associated with catastrophizing. In Alzheimer`s disease with mild cognitive impairment, fear of falling indicators are almost indistinguishable from those of healthy individuals. Data across various clinical groups are heterogeneous, and the phenomenon of fear of falling requires more thorough investigation. This could be beneficial in developing psychocorrection programs for elderly patients and reducing the risk of falling.